Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 75. Beitrag. Coleoptera: Coccinellidae (Nachtrag zum 25. Beitrag). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 1969)
The results of further studies of material from the Zoological Museum in Berlin (coll. Bischoff: 47 individuals of 16 species) and from the Museum G. Frey Tutzing (coll. Mader) are reported. The list contains data about finds of 12 species which had been known from one site only (5) or not at all (7) in Albania. These 6 first finds raise the total of the Coccinellidae known from Albania to 41 species.